A Sublaminate Generalized Unified Formulation for the analysis of composite structures. (10th May 2016) - D'Ottavio, Michele
Abstract: This paper presents a very flexible variable kinematics modeling technique for composite structures. The key point is the subdivision of the multilayered cross-section into numerical sublaminates, each consisting of one or more physical plies, and the formulation of model assumptions independently in each sublaminate according to the compact index notation known as Generalized Unified Formulation. Reference is made to the classical displacement-based and the mixed RMVT variational frameworks. For each sublaminate, the user may thus freely choose the order of the through-thickness polynomial distribution of each unknown as well as whether the unknown is described in an Equivalent Single Layer (ESL) or Layer-Wise (LW) approach. Sublaminates are always assembled in a Layer-Wise manner. This Sublaminate-GUF (S-GUF) is generally applicable to multilayered structures, but is particularly useful for sandwich panels, in which different models may be used for the thick, soft core and the thin, stiff skins. A Navier-type solution is used for demonstrating the validity of this approach by means of benchmark problems concerning the static response of sandwich plates.